History of Philosophy: Between History and Philosophy - Olszewski, Mikołaj (Roczniki Filozoficzne, 2025)
Among Polish historians of philosophy, few can match Stefan Swieżawski in his successful combination of history of philosophy and philosophy itself. However, his works on the history of philosophy demonstrate different patterns of interplay between these two disciplines, which is dependent on their subject matter. For instance, his books and articles on Thomas Aquinas show a pronounced philosophical slant, while those dealing with 15th-century thought demonstrate a historical predilection. In my opinion, this is due to the fact that Swieżawski ascribed much philosophical significance to our contemporary reading of Aquinas.